Radical resection of a craniopharyngioma via the extradural anterior temporal approach with zygomatic arch osteotomy - Ota, Nakao (Surg Neurol Int, 2016)
BACKGROUND: Though the extradural anterior temporal approach (EDATA) with zygomatic osteotomy is useful, there are only few reports of this approach being used for craniopharyngioma resection. Herein, we report our surgical case series and the technical importance of EDATA for the radical removal of a craniopharyngioma. METHODS: We report 7 cases of craniopharyngiomas treated surgically between April 1999 and October 2015. The surgical approaches, clinical presentation, pre and postoperative radiographic examination results, surgical outcomes, and morbidity were analyzed. RESULTS: The mean follow-up period was 89.1 months. The surgical approach was EDATA with zygomatic osteotomy in 4, combined interhemispheric translamina terminalis approach (IHTLA) and trans-sylvian anterior temporal approach (ATA) in 2, and IHTLA in 1 patient. Complete tumor resection was achieved in all cases, without any recurrence during the follow-up period. Transient morbidities were oculomotor nerve palsy in 2, and meningitis and hydrocephalus in 1 patient. There was 1 case of permanent morbidity due to hydrocephalus that needed a ventriculoperitoneal shunt, and 1 case of blindness on the operative side. Visual acuity and visual field improved in 4 cases, showed no change in 2 cases, and deteriorated in 1 case. Though the pituitary stalk was preserved in 2 cases, all 7 cases needed total hormone replacement therapy. CONCLUSION: EDATA with zygomatic osteotomy ensures sufficient mobility of the internal carotid artery, and provides a good lateral and look up operative view. Hence, it can be used effectively for radical resection of craniopharyngiomas through the opticocarotid space and retrocarotid space.